CONSONANT CLUSTERS ACROSS MORPHEME BOUNDARIES: POLISH MORPHONOTACTIC INVENTORY AND ITS ACQUISITION - Zydorowicz, Paulina (Versita Ltd., de Gruyter, 2010)
Morphonotactics is a term introduced by Dressler and Dziubalska-Kołaczyk (2006) to refer to the interaction of phonotactics and morphotactics. This paper examines the acquisition of phonotac- tics and morphonotactics, i.e. consonant clusters occurring within morphemes and across mor- pheme boundaries. It is hypothesized that morphonotactic clusters will be better retained in pro- duction than lexical clusters as they carry significant morphological information. Additionally, the acquisition of consonant clusters will be investigated in terms of markedness. With respect to markedness, two hypotheses have been put forward. Firstly, less marked (preferred) sequences will emerge earlier. Secondly, preferred clusters will be retained in production better.
Keywords: phonotactics; morphonotactics; markedness; language acquisition